Ceramides and sphingomyelinases in senile plaques - Maï Panchal (Neurobiology of Disease, 2014)
The senile plaque is a hallmark lesion of Alzheimer disease (AD). We compared, without a priori, the lipidome of the senile plaques and of the adjacent plaque-free neuropil. The analysis by liquid chromatography coupled with electrospray ionization mass spectrometry revealed that laser microdissected senile plaques were enriched in saturated ceramides Cer(d18:1/18:0) and Cer(d18:1/20:0) by 33 and 78% respectively with respect to the surrounding neuropil. This accumulation of ceramides was not explained by their affinity for Aβ deposits: no interaction between ceramide-liposomes and Aβ fibrils was observed in vitro by surface plasmon resonance and fluorescent ceramide-liposomes showed no affinity for the senile plaques in AD brain tissue. Accumulation of ceramides could be, at least partially, the result of a local production by acid and neutral sphingomyelinases that we found to be present in the corona of the senile plaques.